An Analysis of Student Speaking Competence and Student Speaking Activity at MTsN Nurul Islam Islamic Boarding School - Fazira, Hirodian Nurul; Amri, Zul (Journal of English Language Teaching, 2024)
This research was conducted to find out the level of students speaking competence of grade VIII MTsN Nurul Islam Islamic Boarding School, and the activities undertaken by students to hone their speaking competence. This descriptive research used a qualitative method. The participant consisted of 33 students of grade VIII Nurul Islam Islamic Boarding school. The research instrument are documentation and observation. The documentation used in this research is the score of students speaking examination. While the observation used for analyze the activities of the students. the study instrument comprises the documentation findings, were analyzed using SPSS 26 for Windows and Pearson Product Moments. Based on the research analysis, it was found that the level of students speaking competence is the good level with the mean score was 73.39. on the other hand, there are several speaking activities researcher assumed as support for students speaking competence of MTsN Nurul Islam Islamic Boarding School. In the classroom, teachers initiate discussions to foster active participation and critical thinking, engage students in question-and-answer sessions to reinforce learning, and organize group presentations on specific topics to encourage teamwork and public speaking. Additionally, communication games like "Two Truths and a Lie" are used to maintain interest and improve verbal fluency. Daily activities include bi-weekly public speaking sessions where students present memorized speeches, weekly conversation practices where students engage in dialogues based on provided texts, and regular vocabulary exercises where students learn and use new words in sentences, with periodic assessments to ensure retention.